Decision making and juvenile justice : an analysis of bias in case processing - Tracy, Paul E. (ABC-Clio ebook., 2002)
Based on a comprehensive study of three counties in Texas, this work examines the idea of differential handling of minority youth offenders. Traditional wisdom indicates that minorities are over-represented in the juvenile justice system due to racism and discrimination within the system itself. The author refutes this logic by challenging current studies and examining the results of the Texas study. The findings suggest that minorities are represented in the juvenile justice system in greater numbers than their majority offender counterparts due to their greater involvement in criminal activity, not to any differential treatment they may receive at crucial decision points within the system. This highly controversial study argues for a more thorough examination of the problem as well as the methodologies employed to examine and address it.